Edukasi Duta Wisata Dalam Mempromosikan Dusun Adat Segunung, Carawulung, Wonosalam, Jombang - Aldino, Pravinska (Jurnal Abdimas Komunikasi dan Bahasa, 2022)
Dusun Adat Segunung is known as a traditional village that still holds traditional ceremonies. In addition, the main commodities are coffee (80 hectares of Robusta and Excelsa). Carangwulung Village is the village with the best coffee producers in Jombang Regency with the best excelsa type superior coffee number 2 in East Java. Unfortunately, Dusun Adat Segunung does not yet have a tourism ambassador who is able to promote tourism potential to the wider community. If Dusun Adat Segunung has tourism ambassadors, the economy of the residents of Dusun Adat Segunung will increase. The implementation of community service begins with training, at this stage the proposing team will act as resource persons or resource providers to be able to provide understanding and material about tourism ambassador education in promoting Dusun Adat Segunung, Wonosalam, Jombang. According to, education about tourism ambassadors in the Dusun Adat Segunung community runs smoothly. The community there responded positively regarding the material provided by the service team and was able to follow well. After the counseling was completed, the service team also distributed the materials used during the counseling. With this counseling, it is hoped that the people of Dusun Adat Segunung can form reliable Tourism Ambassadors in order to promote the richness of art, culture and tourism of Dusun Adat Segunung to tourists. The participants already knew about the tourism ambassadors of Dusun Adat Segunung after participating in the socialization. In addition, the participants also began to know how the role of tourism ambassadors in promoting Dusun Adat Segunung.